2016
DOI: 10.1016/j.euroneuro.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of high-dose baclofen for the treatment of alcohol dependence: A multicentre, randomised, double-blind controlled trial

Abstract: Previous randomised placebo-controlled trials with low-to-medium doses of baclofen (30-60mg) showed inconsistent results, but case studies suggested a dose-response effect and positive outcomes in patients on high doses of baclofen (up to 270mg). Its prescription was temporary permitted for the treatment of alcohol dependence (AD) in France, and baclofen is now widely prescribed. Recently, a small RCT found a strong effect of a mean dose of 180mg baclofen. In the present study the efficacy and safety of high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 27 publications
(56 reference statements)
1
86
2
2
Order By: Relevance
“…In three double-blind placebo-controlled clinical trials, alcohol-dependent adults treated with 30–270 mg per day baclofen were more likely to achieve complete abstinence compared to those who received placebo (Addolorato et al, 2002, 2007; Müller et al, 2015). In contrast, four other trials found no significant differences in alcohol abstinence among alcohol-dependent adults given 30–150 mg per day baclofen or placebo (Addolorato et al, 2011; Beraha et al, 2016; Garbutt et al, 2010; Ponizovsky et al, 2015). …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In three double-blind placebo-controlled clinical trials, alcohol-dependent adults treated with 30–270 mg per day baclofen were more likely to achieve complete abstinence compared to those who received placebo (Addolorato et al, 2002, 2007; Müller et al, 2015). In contrast, four other trials found no significant differences in alcohol abstinence among alcohol-dependent adults given 30–150 mg per day baclofen or placebo (Addolorato et al, 2011; Beraha et al, 2016; Garbutt et al, 2010; Ponizovsky et al, 2015). …”
Section: Discussionmentioning
confidence: 84%
“…In one study conducted in baboons, acute doses of baclofen (1.8 and 2.4 mg/kg) reduced self-administration responses for alcohol, decreased total alcohol intake, and facilitated extinction of responding directed towards obtaining alcohol (i.e., alcohol seeking; Duke et al, 2014). Randomized studies to date have shown some promise although treatment efficacy has been mixed (Addolorato et al, 2002, 2007, 2011; Beraha et al, 2016; Farokhnia et al, 2017; Garbutt et al, 2010; Girish et al, 2016; Leggio et al, 2015; Lesouef et al, 2014; Müller et al, 2015; Ponizovsky et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…However, the existing data on its clinical usefulness in humans is equivocal, with three positive810) and three negative1113) randomized controlled trials. Several factors have been examined to explain the inconsistency noted in the response to baclofen.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of higher doses of baclofen was further demonstrated in a double-blind RCT, where doses up to 270 mg/day (mean 180 mg/day) resulted in significant higher abstinence rates compared with placebo 19. However, in a recent study, we could not replicate this finding,20 but there were three important differences between the studies: our dosage was lower (up to 150 mg), patients received cognitive behavioral therapy (CBT) (not in the study of Müller et al ), and had lower drinking levels before treatment. Due to these contrasting results, further studies have to be awaited to draw final conclusions about the efficacy of baclofen in the treatment of AD.…”
Section: Introductionmentioning
confidence: 69%
“…In November 2014, the patient decided to participate in a double-blind, placebo-controlled RCT that was conducted to study the efficacy of high doses of baclofen for the treatment of AD (Nederlands Trial Register, number NTR3681; for a detailed description see Beraha et al 20). The patient met all inclusion and none of the exclusion criteria of that study and informed consent were obtained.…”
Section: Case Presentationmentioning
confidence: 99%